La audaz intelectualidad afro de Teófilo Potes (2020)
Teófilo Roberto Potes is a central figure in the history of the Colombian Pacific region, but his importance and complexity are poorly understood today. The present article suggests that Potes’ life and work merit reconsideration today. By using oral histories of his students, primary sources, and an unknown publication of Potes himself, and by contextualizing them in their moment, the article reconstructs Potes’ biography and sketches the principal elements of his thought. In that way, it traces the importance of a person who, even beyond being the first one to valorize and reveal the Afro-Pacific culture, demonstrates a concept of the African heritage, of the political component of culture, of being a black intellectual, and of the radical horizontality of the Western and Afro-Pacific worlds to be considered in the present historical conjuncture.